PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI MIPA 2 DI SMAN 1 SITUBONDO - Aida Nurul Safitri; Dinda Aulia Mardani; Maryani Maryani; Darwoto Darwoto (JURNAL PEMBELAJARAN FISIKA, 2023)
This research is a classroom action research with the aim of improving students' cognitive learning outcomes in the material of sound waves. The physics material in this even semester for class XI is sound waves. The physical material a fits perfectly with the PBL model. This is evidenced by the increase in learning outcomes with the PBL model. The subjects of this study were all 34 students in class XI MIPA 2 at SMAN 4 Situbondo. Data obtained from the results of learning physics in the form of cognitive tests. qualitative descriptive analysis and gain-test analysis. This research was conducted in two cycles. The conclusion of this study is that the application of the PBL model in physics learning can improve student learning outcomes. This is shown from the results of the average N-Gain score increasing from cycle I to cycle II. Cycle I and cycle II were 0.31 and 0.55 respectively in the moderate category.